Poetic Rhythm in Abū Tammām’s selected anthology - MEBROUK, BEN DAOUD (The International tax journal, 2026)
This article seeks to examine one of the most significant elements in poetry—rhythm—and to explore how Abū Tammām relied on it in the process of selecting and choosing the poetic fragments he included in his book al-Waḥshiyyāt. After conducting a prosodic (ʿarūḍī) analysis of the corpus, we identified a distinctly "Tammāmian " inclination that brings together meter and poetic purpose on the one hand, and, on the other, the prosodic configuration of each meter and the movement it imposes upon rhythmic dynamics.